The Wiley‐Blackwell Handbook of the Psychology of Leadership, Change, and Organizational Development 2013
DOI: 10.1002/9781118326404.ch16
|View full text |Cite
|
Sign up to set email alerts
|

Individual Readiness for Organizational Change

Abstract: This paper is a qualitative review of two concepts: change readiness and resistance to change. We review their use, clarify their conceptual underpinnings, and address the assumption of them being the opposite poles of the same continuum. We juxtapose the two concepts and analyze their dimensions which commonly represent a source of ambiguity about their meaning, review their evolution, and compare them to similar concepts. We argue that resistance to change addresses two important aspects: resistance as behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 103 publications
0
19
0
4
Order By: Relevance
“…Trivette and Raab (2011) for example, found that variations in staffs' receptiveness to the classroom practices constituting the focus of training described in this paper was the best predictor of adoption and use of the practices. The findings, taken together, suggest that variations in readiness to change may be a factor contributing to variations in receptiveness to training (Choi & Ruona, 2013;Peterson, 2012;Peterson & Baker, 2011).…”
Section: Patterns Of Resultsmentioning
confidence: 92%
“…Trivette and Raab (2011) for example, found that variations in staffs' receptiveness to the classroom practices constituting the focus of training described in this paper was the best predictor of adoption and use of the practices. The findings, taken together, suggest that variations in readiness to change may be a factor contributing to variations in receptiveness to training (Choi & Ruona, 2013;Peterson, 2012;Peterson & Baker, 2011).…”
Section: Patterns Of Resultsmentioning
confidence: 92%
“…) Siinä missä yk silön muu tosvalmiuden ajatellaan rakentuvan yksilön asen teista ja uskomuksista (Armenakis ym. 1993), organisaation muutosvalmius pitää sisällään or ganisaation rakenteissa olevan kult tuurin, johta juuden ja viestinnän (Choi & Ruona 2011).…”
Section: Lähijohtajan Muutosvalmiusunclassified
“…Muutokseen liittyvien kielteisten tunteiden vä hentämiseksi on tunnistettu useita erilai sia stra tegioita, muun muassa kouluttamisen, riittävän viestinnän, osallistamisen ja neuvottelukulttuu rin omaksumisella voidaan vähentää muutos vastarintaa, mutta myös kasvattaa keinoja yksi löiden muutosvalmiuden luomiseksi (Kotter & Schlesinger 1979). Merkittävin ero näiden kä sitteiden välillä on se, että muutosvastarinnas ta puhuttaessa yksilöstä puhutaan muutoksen vastaanottajana, kun taas muutosvalmiudessa yksilöllä on aktiivisempi rooli muutoksen koke misessa (Choi & Ruona 2011).…”
Section: Lähijohtajan Muutosvalmiusunclassified
See 2 more Smart Citations